Association of equol producing status with aortic calcification in middle-aged Japanese men: The ERA JUMP study. (1st April 2022) - Zhang, Xiao; Fujiyoshi, Akira; Ahuja, Vasudha; Vishnu, Abhishek; Barinas-Mitchell, Emma; Kadota, Aya; Miura, Katsuyuki; Edmundowicz, Daniel; Ueshima, Hirotsugu; Sekikawa, Akira
Abstract: Background: Equol, an isoflavone (ISF)-derived metabolite by the gut microbiome in certain individuals termed as equol-producers, might be the key anti-atherogenic component of ISFs. Our objective was to determine the association between equol-producing status and aortic atherosclerosis assessed as aortic calcification (AC). Methods: This population-based study of 302 Japanese men aged 40–49, free of cardiovascular disease, examined serum levels of equol and ISFs, AC in the entire aorta by electron-beam computed tomography with Agatston method, and cardiovascular risk factors. We defined equol-producers as individuals with serum levels of equol ≥20 nM and prevalent AC as an AC score ≥ 10. We analyzed the association between equol-producing status and AC using Tobit and logistic regressions. We performed age-stratified analyses since age was a significant effect-modifier. Results: The 70th to 90th percentile AC scores were 4 to 243 in equol-producers and 15 to 444 in non-producers, respectively. Overall, equol-producers (41% of the sample) had lower AC scores (−209, [95% confidence interval (CI): −455, 36]) and odds of AC (odds ratio (OR): 0.7 [95% CI: 0.4, 1.3]), although not statistically significant, compared to non-producers after controlling for cardiovascular risk factors. Among men aged 46–49, equol-producers had significantly lower AC scores (−428 [95% CI: −827, −29]). Furthermore, there were null associations between serum levels of ISFs and both AC score and the odds of AC. Conclusion: In middle-aged Japanese men, equol-producers had a non-significantly lower burden of aortic atherosclerosis than non-producers whereas ISFs had a null association. Studies with larger sample sizes in both sexes are warranted. Highlights: Equol-producers had a lower burden of aortic atherosclerosis than non-producers. There was no association between serum soy isoflavones and aortic atherosclerosis. Equol may be the key anti-atherogenic factor of soy isoflavones.